2022
DOI: 10.20473/jaki.v10i2.2022.188-196
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Team Cohesion and Trust on Team Effectiveness in Preventing Tuberculosis

Abstract: Background: The transmission of tuberculosis (TB) is hard to stop. Surabaya city has the highest TB cases in East Java and only achieved <90% of the target in 2017-2018. The formation of preventing TB team in every primary health care (PHC) is expected to work effectively in preventing TB cases in society. Aims: This study aimed to analyze the impact of cohesion and trust within a team on team effectiveness in preventing TB cases in Surabaya. Methods: This study was an observational study with a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The next topic is health program management. Study by Lestyoningrum, Purwatiningsih and Faisal (2022) reports that team cohesion and trust as a team process have a significant influence on the effectiveness of the TB control team. In addition, Widati et al (2022) found that eight districts/cities in East Java implemented smoke-free regional regulations.…”
mentioning
confidence: 99%
“…The next topic is health program management. Study by Lestyoningrum, Purwatiningsih and Faisal (2022) reports that team cohesion and trust as a team process have a significant influence on the effectiveness of the TB control team. In addition, Widati et al (2022) found that eight districts/cities in East Java implemented smoke-free regional regulations.…”
mentioning
confidence: 99%